Pengembangan LKPD Berbasis STEAM untuk Melatih Kreativitas Siswa dalam Pembuatan Karya Seni Rupa di Kelas III Madrasah Ibtidaiyah - Suherman (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study addresses the low student creativity and scarcity of innovative STEAM-based worksheets in Islamic Elementary Schools (Madrasah Ibtidaiyah). It aims to develop and test STEAM-based worksheets for third-grade visual arts. The research fills the gap between theory and practice by providing a contextual instructional product. Using the R&D method with the 4D model, the study involved expert validation, practicality tests with teachers and students, and effectiveness testing with a pretest-posttest design. Key results show the worksheets were highly valid (average score 3.72), highly practical, and effective in significantly improving creativity (p<0.05) with a large effect size (0.82). The N-Gain score of 0.68 (moderate category) demonstrates meaningful improvement, with the highest growth in originality.